Performance Analysis of Aviation Security Officers (Avsec) in Examination of Passengers and Goods at the Security Check Point of Husein Sastranegara International Airport, Bandung, West Java - Muhamad Irvan; Awan Awan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Employee performance is the result of work achieved by someone in a company with the responsibilities that have been given. The job of an avsec officer is to ensure the security and safety of flights as well as airport service users, therefore it is necessary for an avsec officer who has good skills and understanding in checking passengers and goods at SCP 2 before entering the entrance to the waiting room so that dangerous goods which are prohibited from being carried on uncarried flights. The purpose of this research is to find out how the performance and what are the constraints of avsec officers in inspecting passengers and goods at SCP 2. This research uses qualitative methods with data collection techniques through interviews, observation, and documentation. Data reduction, data presentation, and drawing conclusions are also used as techniques in analyzing data. The results obtained in this study are the performance of avsec officers which include quantity, quality, timeliness, attendance, and the ability to cooperate in inspecting passengers and goods at SCP 2. The performance of avsec officers is in accordance with Regulation General of Civil Aviation No. SKEP/2765/XII/2010 with their respective responsibilities. However, there were still obstacles that occurred during the inspection of passengers and goods at SCP 2, namely the lack of understanding of regulations by airport service users in carrying dangerous goods, which triggered arguments.